2012
DOI: 10.2519/jospt.2012.3942
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Computerized Adaptive Test and Modified Oswestry Low Back Pain Disability Questionnaire: Relative Validity and Important Change

Abstract: 33 PRO surveys, the process of collecting PRO surveys is evolving from paper and pencil 2,20 to computer-administered 31 and computerized adaptive testing (CAT) administration, 8,19,34,49,51 which has stimulated discussion about the strengths and weaknesses of each method of survey administration. The current project focuses on a comparison of selected psychometric properties of measures estimated using 2 PRO surveys, a paper-and-pencil survey 24 and a CAT administration 34 PRO survey, both specific to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…these results are similar to those from Rasch analysis of the RMDQ-24 (16)(17)(18)(19), which have also shown that version of the questionnaire to contain some misfitting items and to have poor targeting of items with high and low activity limitation. therefore, in our view it is timely to reconsider whether: (i) the RMDQ should be reconstructed using an instrument development approach based on item-response theory, including the consideration of different items and response options; or (ii) the use of alternative questionnaires should be recommended, such as the Oswestry Disability Index, that have shown evidence of fitting the Rasch model (33); or (iii) a completely new questionnaire should be developed, perhaps utilizing a computer adaptive testing delivery platform (34).…”
Section: Discussionmentioning
confidence: 99%
“…these results are similar to those from Rasch analysis of the RMDQ-24 (16)(17)(18)(19), which have also shown that version of the questionnaire to contain some misfitting items and to have poor targeting of items with high and low activity limitation. therefore, in our view it is timely to reconsider whether: (i) the RMDQ should be reconstructed using an instrument development approach based on item-response theory, including the consideration of different items and response options; or (ii) the use of alternative questionnaires should be recommended, such as the Oswestry Disability Index, that have shown evidence of fitting the Rasch model (33); or (iii) a completely new questionnaire should be developed, perhaps utilizing a computer adaptive testing delivery platform (34).…”
Section: Discussionmentioning
confidence: 99%
“…32 Using item response theory and computerized adaptive tests to collect outcomes data in routine clinical work is a relatively new concept, but small-and large-scale applications have been described. 10,28,31,37,41 The FS measures estimated by the LCAT were supported for adequate internal consistency reliability (α = .92) 32 ; construct validity 32,37 ; predictive validity 34 ; sensitivity to change 33,37 ; responsiveness 33,37 ; interpretability using levels of minimal detectable change (MDC), minimal clinically important improvement (MCII), and a functional staging model 62 ; and usability. 13,63 The LCAT FS measures are based on a rating-scale item response theory model appropriate for regression techniques that assumes linearity of continuous data.…”
Section: Data Collectionmentioning
confidence: 92%
“…The functional status (FS) outcome measure, developed and used by FOTO, is body region specific, with demonstrated validity and reliability for common musculoskeletal conditions. 11,[15][16][17][18][19][20] Patients enter demographic information into the system and complete a baseline FS measure electronically prior to their evaluation and intervention. At subsequent visits, the therapist and/or administrative staff issue follow-up surveys, including the final discharge FS survey that includes patient satisfaction questions.…”
Section: Description Of Data Sourcementioning
confidence: 99%